2013
DOI: 10.1038/bjc.2013.601
|View full text |Cite
|
Sign up to set email alerts
|

p53 and cell cycle independent dysregulation of autophagy in chronic lymphocytic leukaemia

Abstract: Background:Activation of wild-type p53 with the small molecule sirtuin inhibitor Tenovin-6 (Tnv-6) induces p53-dependent apoptosis in many malignant cells. In contrast, Tnv-6 reduces chronic lymphocytic leukaemia (CLL) cell viability with dysregulation of autophagy, without increasing p53-pathway activity.Methods:Here, we have investigated whether a quiescent phenotype (unique to CLL) determines the Tnv-6 response, by comparing the effects of Tnv-6 on activated and proliferating CLL. We further studied if thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…As this drug inhibits SIRT1 from deacetylating p53 at K382 in several tumor cells stabilizing p53 expression and reactivating its apoptotic function, 4 , 5 , 6 we hypothesized that acetylation of K382- p53 could be as well compromised in Tv6-treated sarcoma cells; however, we found that the antiproliferative effect of Tv6 was independent of the p53 gene status (wild type or mutated), K382- p53 acetylation or apoptotic function. Similar results showing that Tv6 has antitumor activity independent on p53 gene status have been reported for chronic lymphocytic leukemia 21 and gastric cancer models. 22…”
Section: Discussionsupporting
confidence: 86%
“…As this drug inhibits SIRT1 from deacetylating p53 at K382 in several tumor cells stabilizing p53 expression and reactivating its apoptotic function, 4 , 5 , 6 we hypothesized that acetylation of K382- p53 could be as well compromised in Tv6-treated sarcoma cells; however, we found that the antiproliferative effect of Tv6 was independent of the p53 gene status (wild type or mutated), K382- p53 acetylation or apoptotic function. Similar results showing that Tv6 has antitumor activity independent on p53 gene status have been reported for chronic lymphocytic leukemia 21 and gastric cancer models. 22…”
Section: Discussionsupporting
confidence: 86%
“…Tenovin-6 has since been used as an inhibitor of sirtuins, especially SIRT1, and has been demonstrated to have a promising anti-neoplastic effect in vitro and in vivo on various hematopoietic malignancies of both lymphoid and myeloid lineages [913, 15, 18, 19]. However, whether tenovin-6 is effective against DLBCL has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that p53 is a microtubule-associated protein that monitors the status of micro-tubes directly [63]. Although PTX could not induce genetic damage, it can induce formation of aneuploidy and triggers p53 response, stabilizes microtubules by promoting the distribution of microtubules, then arresting the cell cycle at G0/G1 and G 2 /M period [64]. Studies have shown that selenocysteine inhibits the depolymerization of microtubular proteins during mitosis anaphase and interferes with the mitosis of leukemia cells [47].…”
Section: Discussionmentioning
confidence: 99%